2014
DOI: 10.1016/j.jmateco.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A many-to-many ‘rural hospital theorem’

Abstract: We show that the full version of the so-called 'rural hospital theorem' generalizes to many-to-many matching problems where agents on both sides of the problem have substitutable and weakly separable preferences. We reinforce our result by showing that when agents' preferences satisfy substitutability, the domain of weakly separable preferences is also maximal for the rural hospital theorem to hold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Pairwise stability means the lack of a single blocking contract. Roth showed that setwise and pairwise stable solutions coincide and exist for specific substitutable choice functions, and a number of extensions and structural results have been obtained in the follow-up literature [19], [4], [8], [13], [14].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pairwise stability means the lack of a single blocking contract. Roth showed that setwise and pairwise stable solutions coincide and exist for specific substitutable choice functions, and a number of extensions and structural results have been obtained in the follow-up literature [19], [4], [8], [13], [14].…”
Section: Introductionmentioning
confidence: 95%
“…Klaus and Walzl studied special versions of setwise stability under different domain restrictions on substitutable preferences [13]. Klijn and Yazici proved that the rural hospitals theorem holds for substitutable and weakly separable preferences in many-to-many markets [14].…”
Section: Related Literaturementioning
confidence: 99%
“…Chaque organisation possède des membres faisant aussi partie d'autres organisations. Le problème se rapproche alors d'un problème de formation de coalitions avec chevauchement des coalitions [18].…”
Section: Choix Social Informatiqueunclassified
“…Many-to-many extensions of sm (and by implication hr) have been considered in the literature (Roth, 1984b;Roth and Sotomayor, 1990;Sotomayor, 1999;Baïou and Balinski, 2000;Fleiner, 2003;Martínez et al, 2004;Echenique and Oviedo, 2006;Bansal et al, 2007;Kojima andÜnver, 2008;Eirinakis et al, 2012Eirinakis et al, , 2013Klijn and Yazıcı, 2014). These matching problems tend to be described in the context of assigning workers to firms, where each agent can be multiply assigned (up to a given capacity).…”
Section: Many-to-many Stable Matchingmentioning
confidence: 99%